Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 4 - Section 4.9 - Antiderivatives - 4.9 Exercises: 62

Answer

$s(t) = -3cost + 2sint + 2t + 3$

Work Step by Step

Given: $a(t)=3cos t-2sin t$ Thus we have: $v(t) = 3sint - 2(-cost)+C$ $v(t) = 3sint + 2cost + C$ $v(0) = 3sin(0) + 2cos(0) + C$ $v(0) = 3(0) + 2(1) + C$ Given: $v(0) = 4$ $4 = 2+ C$ $2 = C$ Plug in the value of $C$ in the function of $v(t)$. $v(t) = 3sint + 2cost + 2$ $s(t) = 3(-cost) + 2sint + 2t + C$ $s(t) = -3cost + 2sint + 2t + C$ $s(0) = -3cos(0) + 2sin(0) + 2(0) + C$ $s(0) = -3(1) + 2(0) + 2(0) + C$ $s(0) = -3 + C$ Given $s(0) = 0$ $0 = -3 + C$ $C = 3$ Plug in the value of $C$: $s(t) = -3cost + 2sint + 2t + 3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.